Efecto del IHPLUS®BF en la germinación de semillas de Leucaena leucocephala (Lam) de Witt cv. Cunningham - Saray Sánchez-Cárdenas; Joisel Vázquez-Martínez; Dayara Domínguez-Ortega; Ismaray Revueltas-Oramas; Hilda Beatriz Wencomo-Cárdenas (Pastos y Forrajes, 2023)
Objective: To evaluate the effect of inoculation with the biofertilizer IHPLUS®BF on seed germination of Leucaena leucocephala (Lam) de Witt cv. Cunningham.